Residential home heating: The potential for air source heat pump technologies as an alternative to solid and liquid fuels. (November 2016) - Kelly, J. Andrew; Fu, Miao; Clinch, J. Peter
Abstract: International commitments on greenhouse gases, renewables and air quality warrant consideration of alternative residential heating technologies. The residential sector in Ireland accounts for approximately 25% of primary energy demand with roughly half of primary home heating fuelled by oil and 11% by solid fuels. Displacing oil and solid fuel usage with air source heat pump (ASHP) technology could offer household cost savings, reductions in emissions, and reduced health impacts. An economic analysis estimates that 60% of homes using oil, have the potential to deliver savings in the region of €600 per annum when considering both running and annualised capital costs. Scenario analysis estimates that a grant of €2400 could increase the potential market uptake of oil users by up to 17% points, whilst a higher oil price, similar to 2013, could further increase uptake from heating oil users by 24% points. Under a combined oil-price and grant scenario, CO2 emissions reduce by over 4 million tonnes per annum and residential PM2.5 and NOX emissions from oil and peat reduce close to zero. Corresponding health and environmental benefits are estimated in the region of €100m per annum. Sensitivity analyses are presented assessing the impact of alternate discount rates and technology performance. This research confirms the potential for ASHP technology and identifies and informs policy design considerations with regard to oil price trends, access to capital, targeting of grants, and addressing transactions costs. Highlights: Air Source Heat Pumps can offer substantial savings over oil fired central heating. Significant residential air and climate emission reductions are possible. Associated health and environmental benefits are estimated up to €100m per annum. Results can inform policy interventions in the residential market to support change.